2013
DOI: 10.11138/jpm/2013.7.1.012
|View full text |Cite
|
Sign up to set email alerts
|

Carbetocin versus oxytocin in caesarean section with high risk of post-partum haemorrhage

Abstract: SummaryObjectives: the aims of the present study were to compare the haemodynamic effects of oxytocin and carbetocin and to assess the efficacy of these two drugs in terms of blood loss and the additional uterotonic needed in caesarean section at high risk of primary post-partum haemorrhage. Methods: women in the carbetocin group (group A) received a bolus of 100 µg IV; women in the control group (group B) received 20 IU of oxytocin in 1000 ml of 0,9% NaCl solution IV (150 mL/ hour). The main parameter evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 23 publications
7
47
1
2
Order By: Relevance
“…Some studies did note a difference in the need for additional uterotonics when using carbetocin as compared to oxytocin, but these have used oxytocin in more a dilute solution or stopped the oxytocin intravenous administration very shortly after delivery. 4,5 As this is not the routine protocol in our hospital, we do not expect any difference in postpartum hemorrhage. In a later secondary analysis retrospective costs of patients can be compared between both groups in our setting…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies did note a difference in the need for additional uterotonics when using carbetocin as compared to oxytocin, but these have used oxytocin in more a dilute solution or stopped the oxytocin intravenous administration very shortly after delivery. 4,5 As this is not the routine protocol in our hospital, we do not expect any difference in postpartum hemorrhage. In a later secondary analysis retrospective costs of patients can be compared between both groups in our setting…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension has been reported as an important medical event in randomized trials, a hypotensive effect has been described both by oxytocin and carbetocin in randomized studies comparing carbetocin with oxytocin mainly on hemodynamic effects. 4,5 In most studies high doses of oxytocin up to 20 units have been used and resulted in significant hypotension with this high dose of oxytocin. 5 When comparing carbetocin 100 µg with oxytocin 5 IU, hemodynamic side effects have been comparable in both groups, but nausea and vomiting have not been specifically been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although oxytocin is the first line uterotonic drug using for PPH prevention and treatment, carbetocin has been approved for promoting uterine contraction in order to prevent PPH in cesarean section. For the study in high risk PPH from Italy shows blood loss post cesarean section, the drop of hematocrit level and side effects in carbetocin group and oxytocin group are not different while additional uterotonic use is significantly greater in oxytocin group [6]. For the study from Canada reports that blood loss after cesarean section is significantly less in carbetocin group whereas side effects are not different [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although, oxytocin is the drug of choice for PPH prevention, several trials from Italy, Canada, Philippines and United Kingdom and Cochrane Database of Systematic Reviews reported that the use of carbetocin could decrease incidences of PPH and blood transfusion, reduce the additional uterotonic drug use or uterine massage and lower side effects such as nausea and vomiting comparing to oxytocin use [6][7][8][9][10]. However, there was no significant difference in incidence of PPH reported in some researches; therefore the cost and benefit of its use should be considered [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%